Prevalence and Resistance Profiles of Pediatric Enterococcal Isolates: A Five-Year Update from Children’s Medical Center Hospital, Tehran - Bahram Nikmanesh; Sajjad Yazdansetad; Mona Konkori; Mehrzad Sadredinamin; Zohreh Ghalavand; Neda Yousefi Nojookambari (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. In this study, attempts were made to evaluate the frequency of high-level gentamicin-resistant (HLGR) and vancomycin-resistant enterococci (VRE) and the prevalence and antibiotic resistance profile of enterococcal species isolated from pediatric patients referred to Children’s Medical Center Hospital, Tehran, over five years. Materials and Methods. A total of 404 enterococcal isolates from different patients referred to the Children’s Medical Center between March 2016 and March 2021 were included in this cross-sectional study. Antimicrobial susceptibility testing was performed using standard methods according to the guidelines of the Clinical Laboratories Standards Institute (CLSI). Results. Approximately one-third of the enterococcal strains were isolated from urology and intensive care units. 17.3% of the isolates were obtained from outpatient sources. However, 82.7% of the isolates were sourced from inpatient settings. We found that the rates of resistance to ampicillin, penicillin, and vancomycin were twice as high in inpatients as in outpatients. Of the total isolates, 87.4% and 49.3% were identified as HLGR and VRE, respectively. In addition, we identified 2% of the VRE isolates that were not susceptible to linezolid. Nitrofurantoin showed excellent activity against enterococcal isolates in the urine, with a susceptibility rate of 92.5%. Conclusion. The present study reports the highest range of VRE isolated from pediatric patients in Iran. Despite the predominance of HLGR enterococci in our region, vancomycin remains effective against such strains. This study is among the few to demonstrate the incidence of linezolid-insensitive VRE in pediatric patients. Therefore, it is important to evaluate effective infection control measures to prevent linezolid and vancomycin resistance in enterococci.